2022
DOI: 10.12968/bjom.2022.30.8.458
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women's knowledge of venous thromboembolism in Malaysia

Abstract: Background Venous thromboembolism is an acute condition resulting in maternal morbidity and death. Aims This study aimed to assess venous thromboembolism knowledge among pregnant women in Malaysia. Methods A cross-sectional study was conducted among 143 pregnant women recruited via convenience sampling. Data gathered included demographic characteristics and knowledge of venous thromboembolism. The Fisher exact test examined the association between knowledge and outcome factors. Results Of the 143 pregnant wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…They also identi ed shortness of breath, chest pain, slow, shallow breath, and lightheadedness of passing out as the signi cant signs and symptoms of PE. These ndings corroborated previous studies [33,34,36] in other climes, speci cally revealing low VTE and PE knowledge levels. In our study, most of those who claimed to know about PE could not adequately identify its causes, signs, and symptoms, with about 35.1% reporting 'blood clot blocking blood vessels in the heart' as one of the major causes of PE.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They also identi ed shortness of breath, chest pain, slow, shallow breath, and lightheadedness of passing out as the signi cant signs and symptoms of PE. These ndings corroborated previous studies [33,34,36] in other climes, speci cally revealing low VTE and PE knowledge levels. In our study, most of those who claimed to know about PE could not adequately identify its causes, signs, and symptoms, with about 35.1% reporting 'blood clot blocking blood vessels in the heart' as one of the major causes of PE.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the widely recognized signs and symptoms are leg swelling (44.8%), pain and tenderness (26.6) and noticeable skin colour changes (18.8 %), which is in agreement with some previous studies among pregnant women. A Malaysian study (Fen et al) [33] revealed that only about 4.2% of the pregnant population knew about VTE. Another Polish study (Dybowska et al) [34] also showed low awareness of VTE (40%) among their participants.…”
Section: Discussionmentioning
confidence: 99%